Vowel And Consonant Simplification In Speech Disorder: An Analysis Of Segmental Phonology - Wardana, I Ketut; Astawa, Nengah; Soper, I Wayan (International Journal of Linguistics and Discourse Analytics, 2021)
The objective of the study is to investigate the sound simplification of speech output in Broca's aphasics and describe the effect of the alteration within phonological features from the perspective of Sonority Sequencing Principle (SSP). The speech output of two patients was exposed using phonological tasks and recorded with a Sonny voice recorder. The effect of features in substitution sonority was measured with the Wilcoxon's test and acoustic features were analyzed with Praat. The results of the study revealed that the consonant substitution and omission errors in Broca’s aphasia occur in the initial position due to the lesion in the anterior part of the left brain and that the less marked features that are statistically substituted by marked features are not significantly affected by marked features that are substituted by less marked features. The substitution was dominantly influenced by neighboring segments and the sonority violance occured againts the sonority scale